2015
DOI: 10.1002/pmic.201400398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prolyl hydroxylation modifications in mammalian cell proteins

Abstract: Prolyl hydroxylation is a post-translational modification (PTM) that plays an important role in the formation of collagen fibrils and in the oxygen-dependent regulation of Hypoxia Inducible Factor-α (HIF-α). While this modification has been well characterized in the context of these proteins, it remains unclear to what extent it occurs in the remaining mammalian proteome. We explored this question using mass spectrometry to analyze cellular extracts subjected to various fractionation strategies. In one strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…As noted above, hydroxylation modifications of proline residues, and to a lesser extent lysine residues, is a common observation in proteomics datasets that result from the analysis of extracellular tissues. These have been studied for types I and III [ 46 ], type IV [ 47 ], type V [ 46 , 48 ] as well as a range of non-collagenous proteins such as osteocalcin [ 49 , 50 ]. However, exhaustive maps that attempt to span the entirety of type 1 remain elusive due to issues with reproducibility within such proteomics methods.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, hydroxylation modifications of proline residues, and to a lesser extent lysine residues, is a common observation in proteomics datasets that result from the analysis of extracellular tissues. These have been studied for types I and III [ 46 ], type IV [ 47 ], type V [ 46 , 48 ] as well as a range of non-collagenous proteins such as osteocalcin [ 49 , 50 ]. However, exhaustive maps that attempt to span the entirety of type 1 remain elusive due to issues with reproducibility within such proteomics methods.…”
Section: Discussionmentioning
confidence: 99%
“…Prolyl-hydroxylase and asparagine hydroxylase are both members of the oxygen-dependent hydroxylase families whose catalytic properties are dependent upon oxygen, and are viewed as the cellular detectors for oxygen concentration (Schofield and Ratcliffe, 2004). Under hypoxic conditions, the absence of oxygen, which constitutes the substrate for PHDs and FIH, results in a cessation of the hydroxylation process, preventing the binding of HIF-α to the p-VHL (Arsenault et al, 2015; Maxwell et al, 2017). This leads to the build-up of HIF-1α in its stable isomer, translocation across the nuclear membrane and binding to the β- subunit to generate the active HIF dimer.…”
Section: Hif Hydroxylationmentioning
confidence: 99%
“…Approximately 80% of mammalian proteins are modified posttranslationally. For instance, phosphorylation is implicated in cell signaling , acetylation in epigenetics and NDs , ubiquitination in regulation of cellular protein homeostasis , hydroxylation in collagen formation , and glycosylation in the pathophysiology of neurotrauma . The basic findings from studies that demonstrated the role of PTMs in the relevant diseases are summarized in Table .…”
Section: Ptmsmentioning
confidence: 99%